Enhanced transport and favorable distribution of Li-ion in a poly(ionic liquid) based electrolyte facilitated by Li1.3Al0.3Ti1.7(PO4)3 nanoparticles for highly-safe lithium metal batteries. (1st February 2021) - Song, Xianli; Zhang, Haitao; Jiang, Danfeng; Yang, Lipeng; Zhang, Jiahe; Yao, Meng; Ji, Xiaoyan; Wang, Gongying; Zhang, Suojiang
Abstract: Solid-state batteries, which exhibit characteristics including uniform Li deposition, non-flammability and low interfacial resistance, are desirable for novel energy storage devices. Herein, a self-standing, fireproof and electrochemically stable organic-inorganic composite ionogel electrolyte was carefully designed and prepared by using polymerized ionic liquid (PIL), ionic liquid (IL), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium aluminum titanium phosphate (LATP) nanoparticles. The incorporation of LATP nanoparticles into polymer backbone was found to facilitate ionic transport due to the homogenous Li + distribution, which would further boost the ionic conductivity and mechanical properties. In addition, the introduction of IL favored the reduction of interface resistance. Benefiting from the nonflammability, the thermal shrinkage performance of as-prepared electrolyte could stand over a broad operating temperature range. A Li/Li symmetric cell containing optimized PIL-14 wt% LATP could be cycled steadily for over 2000 h at 50 °C. A lithium metal battery containing composite ionogel electrolyte exhibited an outstanding specific capacity of 145 mAh g −1 and 95% capacity retention at 50 °C even after 100 cycles. This study indicates that the co-employment of IL and inorganic nanoparticle is an effective strategy for the construction of organic-inorganic hybrid electrolytes for high-safety solid-state lithium metal batteries (LMBs).